Prototyping of a solar-powered charging station for energy storage applications - Lim, Zhi Wei (2018)
In recent years, sharing economy system businesses are blooming in many countries [1]. Some of the examples that best describes the sharing economy in Singapore will be “Telepod” and “BlueSG” which rents out electric scooters and electric vehicles as the last mile mode of transportation to benefit public users[2, 3]. Similarly renting power bank using a kiosk system On-The-Go (OTG) can be another effective and successful model for the sharing economy. One of the problems faced in the kiosk system is the power supply required to support the system and with increasing demand of system out there, it will be challenging to install the power supply distribution channels from the substation to the rental kiosk system. Therefore, the author has proposed using solar power for the charging station which could make the system more sustainable. As for the hardware implementation, the author has developed a small-scale simulation by building an energy storage kiosk prototype with the integration of solar panel as one of the mode of power supply for charging and auxiliary operations. The charging station was optimised by removal of DC to AC power conversion before the power flow towards the power bank. Overall, solar panel can be the possible solution used in the future for sharing economy with kiosk system.